A droplet microchip with substance exchange capability for the developmental study of C. elegans1. Issue 8 (21st April 2015) - Wen, Hui; Yu, Yue; Zhu, Guoli; Jiang, Lei; Qin, Jianhua
<x xml:space="preserve">Abstract</x> A multifunctional droplet microdevice was presented for the post-embryonic development study of C. elegans initiating from the L1 stage, and the effect of HIF-1 on worm development was investigated.